2017
DOI: 10.1534/genetics.117.300328
|View full text |Cite
|
Sign up to set email alerts
|

Tra-2 Mediates Cross-Talk Between Sex Determination and Wing Polyphenism in Female Nilaparvata lugens

Abstract: Sexual dimorphism and wing polyphenism are important and evolutionarily conserved features of many insect species. In this article, we found a cross-talk linking sexual differentiation with wing polyphenism in the brown planthopper (BPH) (order: Hemiptera). Knockdown of the sex determination gene in () in nymph caused females to develop into infertile pseudomales containing undeveloped ovaries. Whereas males treated with ds exhibited normal morphology, but lost fertility. Knockdown of in adult females (materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Consistent with this, we also find enrichment of hormone signalling amongst genes with male-biased methylation, with 3 insulin genes hypermethylated in males (2 not expressed, 1 has male-specific expression). Insulin receptors determine alternative wing morphs in planthoppers (Xu et al 2015) and have been shown to interact with the core sex determination gene TRANSFORMER-2 (Zhuo et al 2017).…”
Section: Asexual Females and Males Have Distinct Methylation Profilesmentioning
confidence: 99%
“…Consistent with this, we also find enrichment of hormone signalling amongst genes with male-biased methylation, with 3 insulin genes hypermethylated in males (2 not expressed, 1 has male-specific expression). Insulin receptors determine alternative wing morphs in planthoppers (Xu et al 2015) and have been shown to interact with the core sex determination gene TRANSFORMER-2 (Zhuo et al 2017).…”
Section: Asexual Females and Males Have Distinct Methylation Profilesmentioning
confidence: 99%
“…In Bombyx mori , tra2 is essential for the development of the testes (Suzuki et al ., ). In Nilaparvata lugens , maternal RNA interference (RNAi) Nltra‐2 causes female offspring to be strictly long‐winged by influencing genes of the insulin signalling pathway (Zhuo et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal RNAi has been reported to be an efficient method to study gene function in BPH (Xu et al., ; Zhuo et al., ). To determine the function of NlHox3 , we injected dsRNA targeting NlHox3 into virgin female adult BPHs within 2 h after emergence.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that parental RNAi of Dctra‐2 has a great influence on female fecundity and egg hatchability in Diaphorina citri (Yu & Killiny, ). It was also found that offspring wing morphs can be influenced by the maternal RNAi of the NlTra‐2 gene in a sex‐specific manner in N. lugens (Zhuo et al., ). Parental RNAi can last for seven generations in Sitobion avenae (Abdellatef et al., ).…”
Section: Discussionmentioning
confidence: 99%